Results of field studies of snow avalanches on Kunashir Island - D. A. Bobrova (Лëд и снег, 2025)
Notwithstanding the fact that the information about the avalanche danger of Kunashir is widely presented in the literature, there is still a certain deficiency of field data on avalanches on the Island. Obtaining data from field observations of avalanche processes on the Kuril Islands would allow us to improve our understanding of avalanches and supplement the existing avalanche hazard maps with new information. Thus, as a result of the expedition performed in April 2022 on the Kunashir, numerous avalanche deposits were described, most of which were recorded in the area between Cape Remontny and Cape Petrova on the south-east coast of the Island. The degree of avalanche activity for the spring season of 2022 in this area is 3 avalanches per 1 linear kilometer of coastline. The maximum volume of deposits does not exceed 300–400 m3. It has been established that on the north-west coast of the central part of the Island from Pervukhina Bay to Sernovodsky Isthmus the geomorphological, climatic and botanical conditions here are very favorable for the formation of avalanches from the ledges of marine terraces. Based on the data on the snow thickness and the areas of avalanche catchments we can estimate the expected avalanche volumes: the maximum volumes are about 500-800 m3, and the average ones are 200–300 m3. We can also judge the high degree of avalanche activity on the coast from Yuzhno-Kurilsky Cape to Gemmerling Cape. The prevailing north-west direction of the winds in the cold season results in the formation of snow-drift sites on the edge of the slopes. The geomorphological factors of the avalanche formation in this area are very favorable and promote snow accumulation and avalanching. Most of the slope is devoid of stands of trees and represented by herbaceous vegetation or completely devoid of vegetation.